NUMERICAL SIMULATION OF THE RHEOLOGICAL PROPERTIES OF ASPHALT CONCRETE USING THREE-POINT BENDING TESTS. - E.B.Joldasbaev; I.M. Jo‘ramahmudov; S.Q. Raximov (CANADA - SCIENTIFIC REVIEW OF THE PROBLEMS AND PROSPECTS OF MODERN SCIENCE AND EDUCATION, 2025)
The rheological behavior of asphalt concrete plays a critical role in determining pavement performance under traffic and environmental loading. This study presents a combined experimental and numerical investigation into the rheological properties of asphalt concrete using the three-point bending test (3PBT) and finite element modeling (FEM) in ABAQUS. Experimental 3PBTs were performed under controlled temperature and loading rates to characterize the viscoelastic response of asphalt specimens. The resulting data were used to calibrate a generalized Maxwell model implemented via a Prony series in ABAQUS, enabling time- and temperature-dependent simulation of asphalt flexural behavior. The numerical model accurately captured the key mechanical responses, including flexural stiffness, stress distribution, and mid-span deflection under various test conditions. This simulation framework provides a robust method for evaluating asphalt performance, predicting fatigue behavior, and optimizing mix design. The study highlights the effectiveness of integrating laboratory bending tests with numerical rheological modeling to better understand and predict the long-term performance of asphalt pavements.